Konsep Desain Kampung Tematik Berbasis Anggur di Palgunadi Selatan, Semarang Utara - Pipit Skriptianata Putra Pranida; Djudjun Rusmiatmoko; Hetyorini Hetyorini; Wawan Destiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Palgunadi Selatan Village, RT 07/RW 05, Bulu Lor Subdistrict, North Semarang, possesses distinctive local potential in the form of community-based grape cultivation. However, this potential has not yet been systematically integrated into spatial and environmental planning at the neighborhood scale. This community service program aims to identify local potential and environmental constraints, formulate a design concept for a grape-based thematic village, and strengthen collaboration between residents, universities, and local stakeholders. The implementation method employs field observation, identification of potential and problems, environmental analysis, participatory discussions with the community, and formulation of a spatial design concept. The results of the program are presented in the form of a conceptual design for the Grape-Based Thematic Village along Palgunadi Selatan Street, which includes gateway elements, pedestrian pathways, communal seating areas, pergola systems for grape cultivation, neighborhood bridges, vertical planting systems, and security posts. This design concept enhances environmental quality, strengthens the visual identity of the neighborhood, and creates opportunities for community-based economic activities and educational tourism. Furthermore, the program contributes to increased community awareness and participation in environmentally responsive and locally based neighborhood development, supporting the realization of a more organized, attractive, productive, and sustainable urban settlement.